VARIASI BAHASA DI LINGKUNGAN MASYARAKAT BRANTA PASISIR TLANAKAN PAMEKASAN - Kusyairi Kusyairi (Kantor Bahasa Provinsi Maluku Utara, 2022)
ABSTRAK: Language variation language actors. In language which is one of the human communication systems used by society in interacting among humans. Language can also experience developments caused by the sophistication of technology that occurs in the present as happened in the communication of the coastal Branta Community. The language used has its own meaning for people who work as fishermen. This studiy aims to describe the types of language variations that exist in the coastal Branta Community and objectively describe language variation in terms of usage and formality. The data of this research were obtained of the people in the waterside environment. Keyword: variations in language, variations in usage, variations in formality.